Analysis of the presence of pathogens which predict the risk of disease at peri-implant sites through polymerase chain reaction (PCR) Análise por reação em cadeia da polimerase (PCR) da presença de patógenos preditores de risco em sítios periimplantares - Joely Ângela de Oliveira Leitão; José Luiz De Lorenzo; Mario Julio Avila-Campos; Wilson Roberto Sendyk (Sociedade Brasileira de Pesquisa Odontológica, 2005)
The presence of DNA of Actinobacillus actinomycetemcomitans, Porphyromonas gingivalis, and Prevotella intermedia in the peri-implant sulcus samples of 19 partially edentulous patients was analyzed by polymerase chain reaction (PCR) and related to the depth of the peri-implant sulcus, bleeding on probing, and probable risk of disease. Ten of those patients presented a history of periodontal disease and nine of those did not. The DNA amplification of these pathogens was observed in seven samples, of which four were from patients without history of periodontal disease. The results suggest that even when significant inflammatory signs are absent the qualitative detection may indicate risk of peri-implantitis, requiring more strict postoperative control. A presença dos ADN de Actinobacillus actinomycetemcomitans, Porphyromonas gingivalis e Prevotella intermedia em amostras coletadas de sulco periimplantar de 19 pacientes parcialmente desdentados foi analisada pela reação em cadeia da polimerase (PCR). Dentre esses 19 pacientes, dez apresentavam histórico de doença periodontal e nove não apresentavam antecedentes. Os resultados obtidos nesta análise foram relacionados com a profundidade do sulco periimplantar, o sangramento à sondagem e o provável risco de doença. Constatou-se que houve a amplificação do ADN das bactérias-alvo em sete amostras, sendo quatro de pacientes sem histórico de periodontopatia. Este resultado sugere que mesmo na ausência de sinais inflamatórios significantes, essa detecção qualitativa pode indicar risco de periimplantite, requerendo manutenção pós-operatória mais rigorosa.